Stadtentwicklungsprobleme der mittelosteuropäischen EU-mitgliedstaaten - Altrock, Uwe (Raumforschung und Raumordnung | Spatial Research and Planning, 2008)
The transition from socialist to market-oriented economies after 1990 brought about farranging changes in Central European cities with locally and regionally selective effects. The capital areas that profited a lot from those trends were only partly successful in strategically influencing spatial development. Therefore the remarkable upgrading of inner cities was accompanied by unintended effects somewhat similar to known development patterns in the West such as suburban sprawl. After the enlargement of the EU in 2004 and with the upcoming socio-spatial polarisation there is an increasing need for state-funded regeneration strategies that should contribute to overcoming the lack of integrated urban policies prevailing in many of the accession states.